THE INFLUENCE OF BLOCKHOLDER OWNERSHIP , PROFITABILITY, AND FIRM SIZE ON TAX AGGRESSIVITY - Ngurah Budiartha Wicaksana; Lela Nurlaela Wati; Hana Norhamida (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
In Indonesia, foreign direct investment is increasing, but in the field, companies with foreign capital say they are making losses to avoid paying taxes, so this is very counterproductive by opening up foreign investment, but the companies are actually losing money both fiscally and commercially. This research aims to analyze the influence of blockholder ownership , profitability, and firm size on tax aggressiveness. This research uses the data analysis method that will be used in this research, namely partial and multiple regression analysis, where the processing uses descriptive statistical analysis. This research uses computer program tools to manage data in the form of Eviews software version 10 . The research results show that the blockholder ownership variable has no effect on tax aggressiveness, but the profitability and firm size variables do tax aggressiveness. So that service companies are expected to pay more attention to the possibility of tax aggressiveness occurring both internally and externally to the company, and the government to tighten and clarify the contents of regulations regarding tax aggressiveness so that companies truly comply with the obligation to pay taxes